Wenckebach Block due to Hyperkalemia: A Case Report. (3rd January 2011) - Sohoni, Aparajita; Perez, Berenice; Singh, Amandeep
Abstract : Hyperkalemia is a commonly encountered electrolyte abnormality that can significantly alter normal cardiac conduction. Potentially lethal dysrhythmias associated with hyperkalemia include complete heart block and Mobitz Type II second-degree AV block. We report a unique case of Mobitz Type 1 second-degree atrioventricular (AV) block, known commonly as Wenckebach, due to hyperkalemia. The patient's symptoms and electrocardiogram (ECG) evidence of Wenckebach block resolved with lowering of serum potassium levels, with subsequent ECG showing first-degree AV block. This paper highlights an infrequently reported dysrhythmia associated with hyperkalemia that emergency physicians should be familiar with.